Sleep quality and social media use: implications for stress and depression among medical students - Hesti Yuningrum; M. Syairaji; Suryani Agustina Daulay; Bayu Anggileo Pramesona (Universitas Gadjah Mada, 2026)
Purpose: This study aims to analyze the relationship between sleep quality and social media use on stress and depression levels in medical students. Methods: This is a quantitative, cross-sectional study. This study was conducted at FK Unila from June to October 2025. The population in this study was all medical students at FK Unila from the 2022, 2023, and 2024 cohorts, totaling 624 students. Data were collected using the Pittsburgh Sleep Quality Index (PSQI) questionnaire to assess sleep quality, the Bergen Social Media Addiction Scale (BSMAS) to measure social media use, and the Depression Anxiety Stress Scale-21 (DASS-21) to assess stress and depression levels. Data analysis using linear regression. Results: Social media use is a factor that is consistently associated with stress (β = 0.061; p < 0.001). Gender is a significant factor after adjusting for other variables (β = 1.268; p < 0.001), whereas sleep quality is not significantly associated with the outcome (β = 0.078; p = 0.235). Stress is the primary determinant of depression (β = 0.580; p < 0.001), and gender remains a significant covariate after adjustment (β = −0.504; p = 0.042), whereas social media use (β = −0.012; p = 0.181) and sleep quality (β = 0.041; p = 0.381) remained not significantly related to depression both before and after adjusting for confounding variables. Conclusion: Social media use is associated with stress levels among medical students, whereas sleep quality is not. In addition, sleep quality and social media use do not show a significant relationship with depression among medical students.